CONCEPTUAL PRINCIPLES OF DIGITALIZATION OF THE HIGHER EDUCATION SYSTEM IN UKRAINE - KRYMCHAK, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the issue of digitalization of the higher education system in Ukraine. The main advantages of the digital transformation of modern education are identified. These include, in particular, improving the quality of education through the introduction of the latest information technologies, increasing the efficiency of communicative interaction both at the management level and between all participants in the educational process, accessibility and interactivity of learning, ensuring the distance learning process, and integrating the domestic education system into the global educational network. The main regulatory legal acts regulating the process of digitalization in the field of education are studied. It is determined that the process of digitalization of the education system involves not only the implementation and support of the functioning of digital infrastructure - information and communication technologies, global information educational networks, material and technical support of educational institutions, but also the formation of digital literacy in all participants in the educational process without exception. This article analyzes the challenges faced by domestic educational institutions on the path to implementing the digitalization process. Such challenges include the level of material and technical support of higher education institutions, the need to form their own model and strategy of digital transformation, and the moral and psychological aspects of the transition from traditional forms of education to the implementation of educational and scientific activities based on modern digital technologies and new approaches, adaptation of curricula and plans, etc.